Modelo pedagógico para nivelación de conocimientos previo ingreso a la educación superior de los bachilleres de Intag. - Alencastro, Angélica A. (2022)
Based on the social, cultural, and educational difficulties that affect the continuity of higher education of high school graduates in the Intag area, a pedagogical model of knowledge leveling has been developed to improve these levels of inclusion. The design of the model began with the elaboration of the theoretical support and continued with a social, cultural, and educational diagnosis, which was carried out through quantitative research with a descriptive scope; the research involved the participation of students, teachers, directors, and parents from two educational institutions in the rural area of Intag; the survey technique was used to obtain the information, and the results were obtained using descriptive statistics. The diagnosis determined that the factors that have the greatest impact on the lack of continuity in higher education are lack of economic resources, distance to higher education centers, lack of family support and low levels of knowledge. In order to face this problem from the educational dimension: the deficiency in knowledge, the pedagogical model for leveling was designed, which included within the pedagogical management: The objectives, contents, methodology, resources and evaluation, selected based on the contents of the "transformar" test, which is used to assign quotas in higher education careers in the country; as well as, profiles, modality, hours - class, among others; also, the administrative management was included, which details the actions for the implementation and operation of a leveling unit in a host educational institution; which is considered the ideal place to implement this, due to the lack of resources of the students. Finally, it is considered that this academic space will prepare them in a better way and will give them a vision of the future so that students who can overcome other types of barriers can enter the university.